Pengaruh Stock Opname Setiap Bulan Terhadap Pengendalian Obat Oral Kedaluwarsa Di Logistik Farmasi RSI Hasanah Muhammadiyah Mojokerto Periode Januari – Maret 2023 - Ainiy Nur Farida (Jurnal Farmasi Indonesia AFAMEDIS, 2023)
Hasanah Muhammadiyah Mojokerto Islamic Hospital has a mission to provide health services by ensuring quality and patient safety. Pharmaceutical logistics is responsible for and supports the Hasanah Muhammadiyah Mojokerto Islamic Hospital in implementing these principles by managing pharmaceutical supplies and medical consumables (BMHP) and providing pharmaceutical services properly. The pharmacy installation of the Hasanah Muhammadiyah Mojokerto Islamic Hospital requires that drugs be managed effectively and efficiently so that there is no problem with expired drug stocks because it can cause material losses borne by the hospital. This study aims to determine the effect of monthly stock taking on the control of expired oral drugs at the pharmacy logistics of RSI Hasanah Muhammadiyah Mojokerto for the period January to March 2022. The research method used is a retrospective descriptive observational method, this study was conducted by observation, interviews, and discussions. . The results of the study showed that the stock taking carried out every month at the pharmacy logistics of the Islamic Hospital Hasanah Muhammadiyah Mojokerto had an effect on drug control efforts at the hospital. This is supported by the absence of reports of receipt of expired oral drugs that reach the patient, controlled management of oral drugs in pharmacy logistics, the percentage value of expired or lost rupiah value is very small, namely 0.08%.